2019
DOI: 10.1111/cmi.12986
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis impairs host base excision repair by downregulating polymerase β

Abstract: Chlamydia trachomatis infections have been associated with ovarian cancer by several epidemiological studies. Here, we show that C. trachomatis‐infected primary human ovarian epithelial cells display elevated oxidative DNA damage. Base excision repair, an important cellular mechanism to repair oxidative DNA lesions, was impaired in infected primary ovarian and in several other types of cells. Polymerase β was downregulated in infected cells associated with upregulation of microRNA‐499a (miR‐499a). Stabilising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…The presence of chlamydial plasmid-encoded Pgp3 (virulence factor in genital tract) antibody was associated with a doubled risk of ovarian cancer [72]. The mechanistic explanation for the relation between Chlamydia infection and ovarian cancer is based on the observations that infection provokes oxidative DNA damage, the down-regulation of p53 function, and induces DNA double-strand breaks [73,74]. Moreover, chlamydial infection causes an epithelial-to-mesenchymal transition (EMT) in host cells and increases the stemness and CpG methylation of genes.…”
Section: Bacterial Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of chlamydial plasmid-encoded Pgp3 (virulence factor in genital tract) antibody was associated with a doubled risk of ovarian cancer [72]. The mechanistic explanation for the relation between Chlamydia infection and ovarian cancer is based on the observations that infection provokes oxidative DNA damage, the down-regulation of p53 function, and induces DNA double-strand breaks [73,74]. Moreover, chlamydial infection causes an epithelial-to-mesenchymal transition (EMT) in host cells and increases the stemness and CpG methylation of genes.…”
Section: Bacterial Microbiomementioning
confidence: 99%
“…[ 73,74] Proteobacteria and Firmicutes were present in 52% and 22% of ovarian cancer samples, respectively. The Proteobacteria/Firmicutes ratio was significantly increased in ovarian cancer samples…”
Section: Igfbp3 Snp Rs2270628mentioning
confidence: 99%
“…As an obligate intracellular bacteria, CT modifies the host cell environment in order to persist through secretion of proteins into the cytosol which also have a potential pro-oncogenic effect [11,32]. CT infection not only inhibits apoptosis but also, through the production of reactive oxygen species, induces oxidative damage of DNA, the repair of which is also impaired by down regulation of base excision repair and nucleotide excision pathways which will eventually result in double strand breaks in DNA [11,[32][33][34][35]. Telomeres, the protective caps on chromosomes, are also damaged [11,36].…”
Section: Chlamydia Infection Persistence and Inflammationmentioning
confidence: 99%
“…Recent studies have shown that C . trachomatis impairs BER of damaged DNA by down-regulating polymerase beta [6]. Deficiency in BER pathway enables the cells to acquire tumorigenic properties [7].…”
mentioning
confidence: 99%
“…C . trachomatis also changes the miRNA profile of the host cell such as by up-regulating miR-30c or miR-499a targeting DRP-1 and polymerase beta, respectively [6, 33]. Both miRNAs also target p53.…”
mentioning
confidence: 99%